UJI DAYA HAMBAT INFUSA BATANG BROTOWALI (Tinospora crispa (L)) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Suharyanisa; Evarina Sembiring; Ester Saripati Harianja; Sahma Desriani Sinaga (Universitas Sari Mutiara Indonesia, 2021)
Background: Brotowali stems (Tinospora crispa (L)) contain many chemical compounds that are efficacious in curing various diseases. Brotowali stems (Tinospora crispa (L)) contain bitter compounds (Picroretin), alkaloids, tinocrisposide, saponins, columbine, palmatin, kaemferol, and starch. Escherichia coli (Gram negatitve) is a bacterium that causes diarrhea. Research objectives: The purpose of this study was to determine the inhibitory power of brotowali stem infusion on the growth of Escherichia coli bacteria and to determine the effective concentration of brotowali stem infusion on the growth of Escherichia coli. Research method: This research methode uses an experimental methode of agar diffusion method of agar diffusion method to test the antibacterial and infusion of brotowali stems with concentrations of 25%w/v. 50%w/v, and 75%w/v. Results: The results of this study showed that concentrations of 25%, 50%, 75% of brotowali stem infusion had antibacterial inhibition against the growth of Escherichia coli as indicated by the inhibitory diameters of 7,5mm, 7,93mm, 10mm, respectively. Conclusion: The conclusion of this study can be concluded that the infusion of brotowali stems (Tinospora crispa (L)) can inhibit the growth of Escherichia coli bacteria.